Identifikasi Komentar Spam Pada Sosial Media - Zena Lusi; Ayu Eka Saputri; Tri Basuki Kurniawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The use of social media is already powerful and difficult to avoid. Social media users are not only limited to the general public, but also public figures and even economic actors who use social media as a means of marketing. In every post from the account owner, there will always be followers who can give likes and comments. Unfortunately, not all comments are related to the uploaded post. One of the most annoying comments is spam comments. Spam comments are comments that are not clear and contain about business (promos / selling), links or various other things that are promoting something. Using the Naive Bayes algorithm, this study wants to identify spam comments, especially on Instagram social media. Where the data is retrieved using the tools provided by Google. Which is then processed with the Rapidminer application to get the Naive Bayes calculation results.